Assessing the potential spread of Zaprionus tuberculatus (Diptera: Drosophilidae) in the Americas: insights for proactive management and agricultural protection - Viana, José Pedro Cavalcante; Viana, Matheus Cavalcante; Cavalcanti, Fábio André Gomes Silva; Mateus, Rogério Pincela; Bitner-Mathé, Blanche Christine; Garcia, Flávio Roberto Mello; Jobim, Karina; Madi-Ravazzi, Lilian [UNESP]; Rohde, Claudia; Martins, Marlucia Bonifácio; Tidon, Rosana (Oxford University Press (OUP), 2025)
Invasive species pose significant ecological and economic threats globally. Zaprionus tuberculatus Malloch, a drosophilid fruit fly native to the Afrotropical region and Indian Ocean islands, is included in the pest list of the Center for Agriculture and Bioscience (CABI) because it uses fruit as breeding sites and can damage cultivated areas. This fly species extended its range across Europe in the late 20th century; in 2020, it was recorded in South America, and currently, it is widely distributed in Brazil. Here, we assess the potential spreading of Zaprionus tuberculatus in Central and North America based on 2 distinct origins of propagules: from South America and from Europe. To this end, we developed species distribution models using bioclimatic variables and elevation data to project potentially suitable habitats and infer invasion routes. In any case, our results indicate suitability for Z. tuberculatus colonization in Central and North America, including major fruit-producing areas in Central American countries and the United States (Florida and California). The rapid dispersal ability of Z. tuberculatus, coupled with its adaptability to diverse environments, underscores the urgency for proactive monitoring and control measures. Therefore, this study provides valuable insights for developing proactive measures to mitigate the spread of Z. tuberculatus and protect agricultural productivity in the Americas.
Keywords: biodiversity; biological invasion; host fruit; pest control; potential distribution